2009
DOI: 10.1155/2009/698769
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Novel Experimental Therapies for Inflammatory Arthritis

Abstract: Conventional and biologic disease-modifying antirheumatic drugs have revolutionized the medical therapy of inflammatory arthritis. However, it remains unclear as to what can be done to treat immune-mediated chronic inflammation after patients become refractory to these therapies or develop serious side-effects and/or infections forcing drug withdrawal. Because of these concerns it is imperative that novel targets be continuously identified and experimental strategies designed to test potential arthritis interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 130 publications
0
20
0
Order By: Relevance
“…Current Treatments. RA along with other inflammatory autoimmune conditions has been traditionally treated with a combination of glucocorticoids (e.g., prednisolone), gold, and nonsteroidal antiinflammatory drugs [NSAIDs (Malemud, 2009)]. However, treatment with NSAIDs often results in gastric and cardiac side effects and provides only symptomatic relief rather than targeting disease progression (Scott et al, 2010).…”
Section: Luchtefeld Et Al 2010mentioning
confidence: 99%
“…Current Treatments. RA along with other inflammatory autoimmune conditions has been traditionally treated with a combination of glucocorticoids (e.g., prednisolone), gold, and nonsteroidal antiinflammatory drugs [NSAIDs (Malemud, 2009)]. However, treatment with NSAIDs often results in gastric and cardiac side effects and provides only symptomatic relief rather than targeting disease progression (Scott et al, 2010).…”
Section: Luchtefeld Et Al 2010mentioning
confidence: 99%
“…Over-expression of SyK and ZAP-70 are associated with autoimmune disorders [12]. Thus, the finding that Cb1 ubiquitin ligase, an enzyme critical for providing a signal for protein degradation, was a negative regulator of SyK ubiquitination and degradation, also made the polyubiquitination-proteasome pathway (see below) a relevant drug target for RA [13].…”
Section: Spleen Tyrosine Kinase (Syk)mentioning
confidence: 99%
“…The principal role of the proteasome is to regulate the cellular function of completed proteins as well as providing a cellular compartment for the controlled degradation of misfolded proteins regardless of whether or not these proteins are subject to lysosomal-mediated degradation [23]. In that regard, the proteasome pathway has become a foremost target for drug development designed to modulate dysfunctional proteins in cancer [24,25] and in autoimmune disorders [12,26]. This despite the clinical findings, which indicated that patients with hematologic malignancies who initially respond to the proteasome inhibitor, bortezomib, ultimately can become "bortezomib-resistant" [27].…”
Section: The Proteasome Pathwaymentioning
confidence: 99%
“…The nuclear protein, sphingosine kinase-2 (SPHK2) is highly expressed in RA synovial tissue [80]. In a recent study, SPHK2 was shown to be abundantly present in and around the nucleus of RASF and SPHK2 was successfully transferred from the nucleus to the cytoplasm after treating RASF with epidermal growth factor [81].…”
Section: Apoptosis-regulating Kinasesmentioning
confidence: 99%
“…Atacicept was previously shown to inhibit B cell maturation/survival factors B lymphocyte stimulator (BlyS) and APRIL both of which are elevated in RA patients and both of which have been postulated to be potential relevant targets for suppressing B-cell survival and B-cell hyperactivity in RA [80].…”
Section: Apoptotic Responses To Anti-ra Therapiesmentioning
confidence: 99%